(untitled) (Oratio Directa, 2025)
Environmental crises require technical policies as well as ethical and cultural transformation. This qualitative literature study examines environmental da'wah through Qur'anic and Hadith perspectives and considers its relevance to disaster risk reduction. The analysis focuses on the concepts of khalifah or stewardship, amanah or entrusted responsibility, mizan or balance, the prohibition of fasad or destruction, ecological piety, and exemplary action. Qur'an 7:56 prohibits causing destruction after the earth has been set in order, while Qur'an 30:41 links damage on land and sea with human action. A hadith narrated by Muslim regarding planting frames ecological benefit as continuing charity for humans and other creatures. These principles support da'wah that combines sermons, education, community organization, digital communication, waste reduction, tree planting, watershed protection, and responsible resource use. Religious leaders, Islamic organizations, educators, businesses, government, and citizens have distinct but connected responsibilities. The article does not test a da'wah program or establish that particular disasters were caused by specific human actions. It therefore offers a normative communication framework whose effectiveness must be evaluated through measurable behavioral and environmental indicators.